Process theology An introductory exposition - Cobb, John B. (Philadelphia The WEstminster Press, cop., 1976)
Process Theology is an introductory exposition of the theological movement that has been strongly influenced by the philosophies of Alfred North Whitehead and Charles Hartshorne. It offers an interpretation of the basic concepts of process philosophy and
Keywords: Process theology